The Evolution of Competitive Strategies in Global Forestry Industries Comparative Perspectives - Lamberg, Juha-Antti.; Lamberg, Juha-Antti.; Näsi, Juha.; Näsi, Juha.; Ojala, Jari.; Ojala, Jari.; Sajasalo, Pasi.; Sajasalo, Pasi. (World Forests, 2006)
This book presents an analysis of the evolution of competitive strategies within the forestry industry. Although the discussion takes place in a relatively narrow field of business on the global scale, the argument is that the chosen context serves as an illustrative setting for a discussion related to global corporate evolution of firms since the industry studied has only recently entered a stage of development characterized by intensified global competition. Moreover, the global forestry industry provides also an ideal setting for the analysis of the changing dynamics of competition within an industry. We propose that the development within the studied industry serves as a symptomatic illustration of the ongoing development processes in other industries: from a competitive setting characterized by a number of small competitors to one dominated by few large equally strong competitors aiming for a global presence. The implications of the study are not restricted to the forestry industry context alone. They extend to other manufacturing industries displaying similar features to the industry studied: maturity, commodity nature, fragmented industry structure, lack of industry leader, and ongoing concentration process. Thus, our contention is that this book contributes to better understanding of the workings of a number of manufacturing industries through discussion of the evolutionary development within the pulp and paper industry.